Tratamento de efluente de abatedouro avícola visando o reúso da água - Liberatti, Arthur Silva (2018)
In poultry slaughterhouse, there is a very large demand for good quality water and much of that volume is disposed of in waterbodies with high organic matter and solids. In this way, the packing plants are developing studies to reduce the consumption of water resources, as well as to apply techniques for the reuse of water. In this context, the present work evaluated the application of the treatment processes (coagulation / flocculation / sedimentation / filtration) using the organic coagulant tannin and the inorganic aluminum sulfate coagulant, both with and without the anionic polymer, with the objective of evaluating the efficiency between the coagulants and to verify the possibility of water reuse. Therefore, four treatments were performed (S - application of aluminum sulfate, S+P - application of aluminum sulfate with anionic polymer, T - application of tannin and T+P - application of tannin with anionic polymer). The analyzed parameters were: turbidity; apparent color; electric conductivity; total dissolved solids and pH. In general terms, the organic coagulant tannin (T) presented the best results, removing after filtration 99.6% of turbidity against 98.2% of the aluminum sulfate (S), in relation to the apparent color the tannin (T) reached removal of 95.5% after filtration, while aluminum sulfate (S) achieved 91.7% removal. In relation to the total dissolved solids parameter, the coagulants obtained better results with the aid of the anionic polymer, with the T+P treatment being the most effective with 98.1% of removal, while the S+P treatment reached 97.8% of removal. The organic tannin coagulant proved to be very efficient and could be an alternative source in the treatment of reuse water, since besides presenting better results in relation to the inorganic coagulant, it has natural origin, does not generate toxic sludge at the end of the process, facilitating the final disposal of waste from the treatment, being a better choice for the environment and humans.